Isolation of streptococcus tigurinus - a novel member of streptococcus mitis group from a case of periodontitis - Dhotre, Shree V.; Mehetre, Gajanan T.; Dharne, Mahesh S.; Suryawanshi, Namdev M.; Nagoba, Basavraj S. (FEMS Microbiology Letters, 2014)
Streptococcus tigurinus is a new member of the Streptococcus viridians group and is closely related to Streptococcus mitis, Streptococcus pneumoniae, Streptococcus pseudopneumoniae, Streptococcus oralis, and Streptococcus infantis. The type strain AZ_3a(T) of S. tigurinus was originally isolated from a patient with infective endocarditis. Accurate identification of S. tigurinus is facilitated only by newer molecular methods like 16S rRNA gene analysis. During the course of study on bacteraemia and infective endocarditis with reference to periodontitis and viridians group of streptococci, a strain of S. tigurinus isolated from subgingival plaque of a patient with periodontitis identified by 16S rRNA gene analysis, which was originally identified as Streptococcus pluranimalium by Vitek 2. Confirmation by 16S rRNA gene analysis showed 99.39% similarity (1476/1485 bp) with S. tigurinus AZ_3a(T) (AORU01000002). To the best of our knowledge, this is the first report of isolation of S. tigurinus from the oral cavity of a periodontitis patient.
Keywords: periodontitis; Streptococcus tigurinus; VGS

Investigation of microbial diversity in geothermal hot springs in Unkeshwar, India, based on 16S rRNA amplicon metagenome sequencing - Mehetre, Gajanan T.; Paranjpe, Aditi; Dastager, Syed Gulam; Dharne, Mahesh S. (Genome Announcements, 2016)
Microbial diversity in geothermal waters of the Unkeshwar hot springs in Maharashtra, India, was studied using 16S rRNA amplicon metagenomic sequencing. Taxonomic analysis revealed the presence of Bacteroidetes , Proteobacteria , Cyanobacteria , Actinobacteria , Archeae , and OD1 phyla. Metabolic function prediction analysis indicated a battery of biological information systems indicating rich and novel microbial diversity, with potential biotechnological applications in this niche.

Inhibition of quorum sensing, motility and biofilm formation ofpseudomonas aeruginosaby copper oxide nanostructures - Desai, Dnyanada G.; Swarali, H.; Navale, Govinda R.; Prabhune, A.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Cluster Science, 2020)
Quorum sensing (QS) is the communication between bacterial cells governed by their population density and regulated by the genes controlling virulence factors and biofilm formation. Multiple mechanisms of biofilms are resistive to antimicrobial chemotherapy; therefore novel strategies are required to overcome its limitations. Here, we report the effect of various copper oxide nanostructures (CuO-NSs) on quorum sensing inhibition. The two-dimensional CuO-NSs such as interlaced nanodiscs, nanodiscs and leaf-shaped nanosheets are prepared via a simple chemical method. The Quorum sensing inhibition (QSI) activity of all the CuO-NS are examined using reporter strainChromobacterium violaceumCV026 andEscherichia colipSB1142. We found that the CuO-interlaced nanodisc structures exhibit better QSI activity than nanodiscs and leaf-shaped sheets. The interlaced nanodisc structures are inhibited various long-chainN-acyl homoserine lactones (AHLs) mediated QS individually and confirmed by other QS-associated phenomena forPseudomonas aeruginosa, including biofilm inhibition, inhibition of virulence factors such as pyocyanin, protease production and swarming motility. Thus QSI activity of CuO-NSs is solely dependent on specific shape offering large surface area and more active sites. The CuO-NS is effective quorum sensing inhibitors, which has potential clinical applications in the management ofP. aeruginosaassociated infections.
Keywords: aeruginosa; Biofilm; Nanostructures; P; quorum sensing; Virulence factors

Isolation of potent alpha-glucosidase inhibitor from a novel marine bacterium Arthrobacter enclensis - Mawlankar, Rahul B.; Dharne, Mahesh S.; Dastager, Syed G. (SN Applied Sciences, 2020)
Alpha-glucosidases are involved in the hydrolyzation of glycosidic bond of di- or oligo-saccharides into mono-saccharides, thus help in the breakdown and absorption of sugars. Inhibition of alpha-glucosidases by inhibitors tend to slow break down and release of sugars into the bloodstream and can be used as therapeutic agents in the treatment of diabetes and obesity. In particular, some of the inhibitors are used in the treatment mainly acarbose, voglibose, and miglitol. In this study, we have reported the alpha-glucosidase inhibitory compound from a newly described marine bacterium Arthrobacter enclensis. The purified compound from A. enclensis was identified by HPLC, and further FTIR and tandem mass spectrometry (MS/MS) methods. The purified compound was annotated and identified by a Web tool CFM-ID (Competitive Fragmentation Modeling for Metabolite Identification). From analysis it was found that the compound showed high similarity with acarbose which is a C7N aminocyclitol compound. Further, we analyze the draft genome of A. enclensis using anti-SMASH. We observed that it matches the homology with biosynthetic gene cluster of acarviostatin and acarbose with 11% and 7% respectively. We demonstrated that, the purified compound from A. enclensis shows the inhibitory activity against alpha-glucosidase with an IC50 value of 500 ± 0.142 μg/ml as compared to standard acarbose, which showed an IC50 value of 200 ± 0.012 μg/ml. This result suggests that A. enclensis has a tendency to produce a C7N aminocyclitol like molecule which matched to acarbose and it uses different biosynthetic gene cluster for the synthesis of C7N aminocyclitol like molecule, which can be further used for the production and treatment purpose.

Insights from a pan India Sero-epidemiological survey (Phenome-India Cohort) for SARS-CoV2 - Naushin, Salwa; Sardana, Viren; Ujjainiya, Rajat; Bhatheja, Nitin; Kutum, Rintu; Bhaskar, Akash Kumar; Pradhan, Shalini; Prakash, Satyartha; Khan, Raju; Rawat, Birendra Singh; Tallapaka, Karthik Bharadwaj; Anumalla, Mahesh; et al. (eLife, 2021)
To understand the spread of SARS-CoV2, in August and September 2020, the Council of Scientific and Industrial Research (India) conducted a serosurvey across its constituent laboratories and centers across India. Of 10,427 volunteers, 1058 (10.14%) tested positive for SARS-CoV2 anti-nucleocapsid (anti-NC) antibodies, 95% of which had surrogate neutralization activity. Three-fourth of these recalled no symptoms. Repeat serology tests at 3 (n = 607) and 6 (n = 175) months showed stable anti-NC antibodies but declining neutralization activity. Local seropositivity was higher in densely populated cities and was inversely correlated with a 30-day change in regional test positivity rates (TPRs). Regional seropositivity above 10% was associated with declining TPR. Personal factors associated with higher odds of seropositivity were high-exposure work (odds ratio, 95% confidence interval, p value: 2.23, 1.92-2.59, <0.0001), use of public transport (1.79, 1.43-2.24, <0.0001), not smoking (1.52, 1.16-1.99, 0.0257), non-vegetarian diet (1.67, 1.41-1.99, <0.0001), and B blood group (1.36, 1.15-1.61, 0.001).

Integrated chemo and bio-catalyzed synthesis of 2,5-furandicarboxylic acid from fructose derived 5-hydroxymethylfurfural - Parate, Roopa D.; Dharne, Mahesh S.; Rode, V. Chandrashekhar (Biomass & Bioenergy, 2022)
Biomass being a renewable source of energy, has emerged as an attractive target for manufacturing valuable products. These possibilities can be explored to meet the current need for degradable plastic, 2,5-furandicarboxylic acid (FDCA). Integration of chemical and biological approaches for direct biomass conversion into FDCA was evaluated in this study. 5-hydroxymethylfurfural (5-HMF) was chemo-catalytically obtained from fructose using recyclable amberlyte IR-120 as a catalyst with >98% purity. Klebsiella oxytoca NCIM 2694 bacterial strain showed the potential of converting 98% of 5-HMF into FDCA with 58% selectivity at 96 h. With optimized conditions of pH 7, 37 degrees C, 2 g whole cells, we reported 99% 5-HMF conversion to FDCA with 95% selectivity at 72 h and 2667 mg L-1 yield, with 39 mg L-1 h-1 productivity. This is the highest yield obtained with the substrate concentration as high as 3000 mg L-1 reported till date. While the bacterial tolerance to 5-HMF observed was for the highest 5-HMF concentration of 4000 mg L-1, with 99% conversion however, compromising the FDCA yield to 2447 mg L-1 and 32 mg L-1 h-1 productivity. Atom economy of 85% and E factor of 17.71 g g-1 was obtained as a measure of its efficiency and sustainability of the process. The developed process will decrease the cost by excluding any extra nutrient supplement, complete substrate utilization, highest FDCA selectivity/productivity and higher tolerance by K. oxytoca, sequentially catalyzing the oxidations by a single route for FDCA synthesis from renewables.
Keywords: biocatalysis; Biodegradable polyester; Biomass; Platform chemical; Sustainability metrics

Investigation of cold-active and mesophilic cellulases: opportunities awaited - Chavan, Sambhaji; Shete, Ashvini; Mirza, Yasmin; Dharne, Mahesh S. (Biomass Conversion and Biorefinery, 2023)
In the recent decade, the global demand and fuel prices have urged a need to track down an alternate resource. Second-generation (2G) biofuel from the lignocellulosic biomass (LCB) is trending as the fundamental alternative resource. Although LCB is the most abundantly available renewable resource, its commercialization into 2G biofuel technology is a major challenge. Efficient LCB hydrolysis requires a proper lignocellulolytic enzyme cocktail. In view to addressing this problem, several researchers are investigating for efficient enzymes to hydrolyze LCB. To date, there are very few commercial enzymes that aid in the breakdown of LCB, and these enzymes are traditionally isolated from culturable microbes. As only 1% of the microbes can be cultivated in the laboratory, the potentials of the uncultured remain under-explored. In the recent decade, advances in metagenomics using next-generation sequencing (NGS) technologies have revealed the vast diversity of hydrolytic enzymes and multiple domain proteins in the ecosystem. Aiming this, we focus our review on investigating efficient cold-active and mesophilic cellulases from the metagenome. India is an agro-based country with various climatic regions, ranging from warm and humid in the south to mild or moderate and cold or snowy in the Himalayan north; therefore, both cold-active and mesophilic cellulases are needed for LCB to ethanol. Along with downsizing, the conversion cost of LCB to fermentable sugars not only increases the enzymatic conversion but also increases the fermentation efficiency, which ultimately helps to commercialize the second-generation biofuel technology. Metagenomics is an evolving concept, and it has opened new horizons for the discovery of micro-organisms and new enzymes.
Keywords: cellulases; Glycosyl hydrolase; Lignocellulosic biomass; Metagenomics; simultaneous saccharification and fermentation

Integrated genomic and functional analysis of Streptomyces sp. UP1A-1 for bacterial wilt control and solanaceae yield increase - Kaari, Manigundan; Manikkam, Radhakrishnan; Joseph, Jerrine; Krishnan, Sakthivel; Annamalai, Kishore Kumar; Khan, Abujunaid; Rajput, Vinay; Dastager, Syed Gulam; Dharne, Mahesh S.; Umar, Md; Venugopal, Gopikrishnan; Alexander, Balamurugan (Gene Reports, 2024)
<em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Ralstonia solanacearum<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> is one of the most destructive soil-borne pathogen, causing bacterial wilt to the solanaceae vegetables. <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 isolated from healthy solanaceae rhizosphere soil, exhibited the lowest disease incidence and increased fruit yield of solanaceae vegetables. However, the genomic and functional properties of UP1A-1 are unclear. Therefore, we conducted the present study to elucidate the genomic characteristics of UP1A-1 by whole genome sequencing. The results indicate that the genome of <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Streptomyces<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> sp. UP1A-1 consists of 8,252,902 bp and contains 72.42 % G + C. We identified the genes that confer plant growth promoting (PGP) function, which include those involved in siderophore production, indole-3-acetic acid biosynthesis, phosphate solubilization, nitrogen metabolism, and potassium metabolism. We also identified several other genes, such as chitinase, peroxidase, superoxide dismutase, catalase, proline biosynthesis, and glucose dehydrogenase, which are believed to be involved in the control of wilt disease. These genes revealed that the strain UP1A-1 has physiologically adapted to varied environmental conditions and could potentially control both abiotic and biotic stresses.